No evidence for a role of the catechol-O-methyltransferase pain sensitivity haplotypes in chronic widespread pain. Issue 11 (22nd June 2010) - Nicholl, Barbara I; Holliday, Kate L; Macfarlane, Gary J; Thomson, Wendy; Davies, Kelly A; O'Neill, Terence W; Bartfai, Gyorgy; Boonen, Steven; Casanueva, Felipe; Finn, Joseph D; Forti, Gianni; Giwercman, Aleksander; et al.
Abstract : Objectives: The aim of this study was to investigate the association between the catechol-O-methyltransferase (COMT) 'pain sensitivity' haplotypes and chronic widespread pain (CWP) in two distinct cohorts. Methods: Cases of CWP and controls free of pain were selected from two population-based studies: the Epidemiology of Functional Disorders study (EPIFUND) (UK) and the European Male Ageing Study (European). The number of cases and controls were 164 and 172, and 204 and 935, respectively. Identical American College of Rheumatology criteria were used in both studies to ascertain CWP status. The EPIFUND study had three time points and cases were classified as subjects with CWP at two or three time points and controls as those free of pain at all three time points. Four single nucleotide polymorphisms (SNP): rs6269, rs4633, rs4818 and rs4680 (V158M) were genotyped using Sequenom technology. Allele and genotype frequencies were compared and haplotype analysis was conducted using PLINK software. Results: No differences in allele or genotype frequencies for any of the four SNP were observed between cases and controls for either cohort. Haplotype analysis also showed no difference in the frequency of haplotypes between cases and controls. Conclusions: There was no evidence of association between the COMT 'pain sensitivity' haplotypes and CWP in two population-based cohorts.